Hegel and the question of postmetaphysical thinking: A study on Heidegger’s and Adorno’s reception of Hegel’s - Fabo Lanuza, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The contemporary reception of Hegel’s concept of negativity is shaped by an effort to disentangle the above said concept from its function within the construction of absolute idealism. Such is the main operation with which, of different way, Heidegger and Adorno coincide. What tries to be shown is, nevertheless, that far from overcoming Hegel, this operation liberates, rather, the conditions of not unilateral access to the genuine Hegelian concept of negativity, and that in this effect the Adornian and Heideggerian reconstruction of the negativity are complementary. The reading of Hegel which becomes thus possible should cast, at the same time, a new light on the conflict between dialectics and hermeneutics within the battlefield of post-metaphysical thinking, and insofar a starting point from which to revisit the Kantian question concerning the problem of metaphysics.